2017
DOI: 10.2174/1381612823666170714161703
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Immune Component of Tumor Microenvironment in the Efficiency of Cancer Treatment: Perspectives for the Personalized Therapy

Abstract: Despite significant progress in cancer diagnostics and development of novel therapeutic regimens, successful treatment of advanced forms of cancer is still a challenge and may require personalized therapeutic approaches. In this review, we analyzed major mechanisms responsible for tumor cells chemoresistance and emphasized that intratumor heterogeneity is a critical factor that limits efficiency of cancer treatment. Intratumor heterogeneity is caused by genomic instability in cancer cells, resulting in the sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 0 publications
1
25
1
3
Order By: Relevance
“…M2 macrophages are a promising therapeutic target . CCR2 or CSF‐1R inhibition has been considered to prevent recruitment of M2 macrophages to the TME or proliferation of TAM .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…M2 macrophages are a promising therapeutic target . CCR2 or CSF‐1R inhibition has been considered to prevent recruitment of M2 macrophages to the TME or proliferation of TAM .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the biological malignancy of tumor cells and the influence of genetic characteristics on sensitivity to therapeutic agents, the immune condition of the tumor microenvironment (TME), consisting of varieties of immune cells, was recently recognized to modulate the efficiency of chemotherapy . Among the components of the TME, tumor‐infiltrating macrophages (TAM) have been reported to contribute to chemoresistance by modulating the cytotoxicity of tumor‐infiltrating T cells .…”
Section: Introductionmentioning
confidence: 99%
“…Evasion of programmed cell removal by the innate immune system plays a critical role in tumor development and progression. [5][6][7][8][9][10][11] Recent studies have revealed that tumor cells upregulate "don't-eat-me" signals to prevent phagocytosis, thus acquiring a survival advantage. [12][13][14] CD47 is an anti-phagocytic ligand broadly expressed on platelets, erythrocytes, and lymphohematopoietic cells.…”
Section: Introductionmentioning
confidence: 99%
“…ных клеток. В настоящее время значение клеточного состава и функциональной ориентации (поляризации) опухолевого микроокружения для клинического течения онкологических заболеваний и ýффективности проводимого противоопухолевого лечения обосновано целым рядом работ [7][8][9][10][11].…”
Section: __________________________unclassified